2020
DOI: 10.1186/s13195-020-00594-6
|View full text |Cite
|
Sign up to set email alerts
|

A computerized version of the Short Form of the Face-Name Associative Memory Exam (FACEmemory®) for the early detection of Alzheimer’s disease

Abstract: Background Computerized neuropsychological tests for early detection of Alzheimer’s disease (AD) have attracted increasing interest. Memory for faces and proper names is a complex task because its association is arbitrary. It implicates associative occipito-temporal cerebral regions, which are disrupted in AD. The short form of the Face-Name Associative Memory Exam (FNAME-12), developed to detect preclinical and prodromal AD, asks individuals to learn the names and occupations associated with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 49 publications
(97 reference statements)
4
46
0
Order By: Relevance
“…The FNAME is an associative memory test sensitive to early changes in AD, which has been associated with Aβ and CSF tau accumulation in clinically normal [7,9], SCD [10], and MCI [11]. Our aim was to explore whether the LAS-FNAME can help identify individuals at increased risk for developing AD by differentiating between cognitively intact PSEN1 mutation carriers and non-carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FNAME is an associative memory test sensitive to early changes in AD, which has been associated with Aβ and CSF tau accumulation in clinically normal [7,9], SCD [10], and MCI [11]. Our aim was to explore whether the LAS-FNAME can help identify individuals at increased risk for developing AD by differentiating between cognitively intact PSEN1 mutation carriers and non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…The FNAME is a highly demanding, associative memory test, which tracks memory changes along the AD-spectrum [ 6 8 ] that has been shown to be correlated with Aβ accumulation in clinically normal older adults [ 7 , 9 ] and adults with subjective cognitive decline (SCD) [ 10 ]. Recent evidence also showed that performance on a computerized version of the FNAME was associated with cerebrospinal fluid levels of amyloid, phosphorylated tau, and total tau in clinically normal and mild cognitive impairment (MCI) [ 11 ]. Importantly, the FNAME engages memory network regions, including the hippocampus, and default mode network regions that are affected early in the disease process [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, AD patients were classified into three clinical categories: cognitively unimpaired (CU), mild cognitive impairment (MCI), and dementia patients [16]. AD is now recognized as a continuum of neurological decline that can be identified and staged through a combination of neuropathological findings and in vivo biomarkers [17,18]. This has led to a paradigm shift in the diagnosis of AD, opening new windows of opportunities for early treatment in the preclinical stages.…”
Section: Novel Biomarkers In the Diagnosis Of Alzheimer's Diseasementioning
confidence: 99%
“…Loss of associative memory (AM), which is the binding of contextual information to stimulus attributes, is commonly considered an early and prominent feature of AD [7]. Measures of AM, which are most vulnerable to AD's pathological processes, are correlated with cerebrospinal fluid markers of AD neurodegeneration [8]. Thus, AM is a critical measure that reflects the efficacy of novel treatment of AD.…”
Section: Introductionmentioning
confidence: 99%